Niger : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2009)
This Selected Issues Paper and Statistical Appendix for Niger are discussed. The Nigerien economic outlook has been improving since 1999. After a long period of decline in per capita income, growth accelerated through 2007, attaining an annual average of 4 percent, or about 1 percent in per capita terms. Economic reforms and political stability have attracted external aid and higher domestic and external private investment. The Equilibrium Real Exchange Rate Approach indicates a moderate undervaluation of 0.7 percent to 3.7 percent.